Essential atlas of gastroenterology and hepatology for primary care - Feldman, Mark (Blackwell Science, 1998)
Univ. of Texas, Dallas. A collection of more than 600 images that pictorially displays the diseases of the gastrointestinal tract, liver, biliary tree, and pancreas in both adults and children. 103 contributors, 94 U.S. DNLM: Gastrointestinal Diesases--atlases.
Keywords: gastroenterologie; Gastroenterology; hepatologie